India: apremier destination for outsourcing - Chorghade, Mukund S.; Chorghade, V. M.; Gurjar, Mukund K.; Ramana, Chepuri V.; Kamerkar, A. V.; Zafran, H.; Mashelkar, Raghunath Anant (Speciality Chemicals Magazine, 2005)

Investigation of magnetic anisotropy in Co nanoparticles using ferromagnetic resonance technique - Sendilkumar, A.; Kasture, Manasi; Patel, Pitamber; Ramana, Chepuri V.; Bhagavatula L. V. Prasad; Srinath, S. (Journal of Physics: Conference Series, 2010)
Using ferromagnetic resonance (FMR) technique, we have investigated the temperature dependence and angular dependence of line width and resonance magnetic field of Co nanoparticles capped with novel alkane carboxylic acids of varying chain lengths. The magnetic properties such as blocking temperature and anisotropy sensitively depend on the chain length as evidenced by the temperature dependence of line width. These results indicate that the magnetic properties of these samples are critically governed by the interparticle interactions which are decided by the chain length. The presence of anisotropy even up to very high temperature above the blocking temperature observed in these studies confirms the presence of inter-particle magnetic interactions as well as intra-particle exchange interaction between the core and shell regions as evidenced by our earlier ac susceptibility and transverse susceptibility measurements on similar system.

InCl3-mediated addition of indole to isatogens: an expeditious synthesis of 13-deoxy-isatisine A - Kumar, Chepuri V. Suneel; Puranik, Vedavati G.; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
A strategy directed towards the total synthesis of isatisine A that involves several late-stage metal-catalyzed transformations that address the key carboncarbon and carbonheteroatom bond formations has been developed. As a part of this strategy, methods for the addition of indoles to isatogens that lead selectively to either 2,2-disubstituted N-hydroxyindolin-3-one or 2,2-disubstituted indolin-3-one compounds have been developed by employing InCl3 as a catalyst or as the reagent. The present methods provide the first examples of the additions of indoles to the isatogen nucleus. To demonstrate its viability, the synthesis of 13-deoxy-isatisine A has been completed in ten steps from a known and easily available lactone.
Keywords: indium; indoles; isatogens; Natural products; Total synthesis

Ir(III)-catalyzed carbenoid functionalization of benzamides: synthesis of N-methoxyisoquinolinediones and N-methoxyisoquinolinones - Phatake, Ravindra S.; Patel, Pitambar; Ramana, Chepuri V. (Organic Letters, 2016)
A mild and efficient Ir(III)-catalyzed C-H carbenoid functionalization strategy has been developed to access. N-methoxyisoquinolinediones and N-methoxyisoquinolinones. The reaction proceeds efficiently in high yield at room temperature over a broad range of substrates without requirement of any additional oxidants or a base.

Ir(III)-catalyzed synthesis of isoquinoline N-oxides from aryloxime and alpha-diazocarbonyl compounds - Phatake, Ravindra S.; Patel, Pitambar; Ramana, Chepuri V. (Organic Letters, 2016)
An efficient Ir(III)-catalyzed C-H activation and annulations of aryloxime with a-diazocarbonyl compounds has been developed for the synthesis of substituted isoquinoline N-oxides. The reaction proceeds under mild atmospheric conditions, without any external oxidants and releases N-2 and H2O as the byproducts. In addition, synthetic applications of the N-oxide products have been established by performing further functionalization. An interesting dimeric iridacyclic complex allied through a bis-silver carboxylate bridge has been isolated that efficiently catalyzed the reaction.

Interrupting base-mediated benzofuran ring transformation with michael acceptors - Srinivas, Kolluru; Sharma, Rashmi; Ramana, Chepuri V. (Journal of Organic Chemistry, 2017)
A simple two-stage approach for the synthesis of 3-(2-arylbenzofuran-3-yl)propanoates and propanamides has been developed employing simple acrylates and acrylamides and readily available 3-aroylbenzofurans. The key step of this process involves a base-mediated ring opening of the 3-aroylbenzofurans and subsequent Michael addition of the resulting 1,3-dicarbonyl intermediate with acrylate/acrylamide, followed by the deformylation in one-pot. The resulting products undergo an acid-mediated dehydrative cyclization to arrive at these targets.
Keywords: Acyl Benzylic Bromides; Beta-Ketoaldehydes; Efficient Synthesis; Ortho-Hydroxybenzyl Ketones; Phenols; Position; Precursors; Sur Le Benzofuranne; Transposition

Iridium(III)-catalyzed alkynylation of 2-(Hetero)arylquinazolin-4-one scaffolds via C-H bond activation - Rohokale, Rajendra S.; Kalshetti, Rupali G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
The directed C-H alkynylation of 2-(hetero)arylquinazolin-4-ones has been explored with the ethynylbenziodoxolone reagent TIPS-EBX employing an Ir(III) catalyst. Complementary conditions for either monoalkynylation or dialkynylation have been developed. Also demonstrated is the broad scope of this reaction and the compatibility of various functional groups such as -F, -Cl, -Br, -CF3, -OMe, -NO2, and alkyl, etc.

Intramolecular nitrone interrupted click reaction - Pothi, Tejas A.; Ramana, Chepuri V. (Organic Letters, 2024)
We document the intramolecular interception of a Cu-catalyzed azidoalkyne cycloaddition employing a suitably placed nitrone group, providing a simple route to the unprecedented spiro-polyheterocyclic scaffold. The reaction is comprised of a Cu-catalyzed [3 + 2]-cycloaddition of (2-azidoaryl)isatogen with a terminal alkyne and the intramolecular trapping of the transient Cu-triazolide intermediate with the isatogen, with a net formation of one C-C and two C-N bonds and the new heterocyclic ring being spiro-annulated.